Mathematical Models in the Manufacturing of Glass C.I.M.E. Summer School, Montecatini Terme, Italy 2008 - Farina, Angiolo. (C.I.M.E. Foundation Subseries ;, 2011)
This volume presents a review of advanced technological problems in the glass industry and of the mathematics involved. It is amazing that such a seemingly small research area is extremely rich and calls for an impressively large variety of mathematical methods, including numerical simulations of considerable complexity. The problems treated here are very typical of the field of glass manufacturing and cover a large spectrum of complementary subjects: injection molding by various techniques, radiative heat transfer in glass, nonisothermal flows and fibre spinning. The book can certainly be useful not only to applied mathematicians, but also to physicists and engineers, who can find in it an overview of the most advanced models and methods. .